434 TAKOTSUBO SYNDROME AFTER PACEMAKER IMPLANTATION. (15th December 2022) - Bastianoni, Gianmarco; Paolini, Federico; Brugiatelli, Leonardo; Alfieri, Michele; Belleggia, Sara; Torselletti, Lorenzo; Coraducci, Francesca; Coretti, Francesca; Principi, Samuele; Stronati, Giulia; Barbarossa, Alessandro; Ciliberti, Giuseppe; et al.
Abstract: Introduction: Takotsubo syndrome is a clinical syndrome characterized by typical anamnestic features together with typical ECG and echocardiographic findings. Comparing with the available literature not so many cases of takotsubo syndrome after pacemaker implantation can be found. Furthermore, there are only few articles talking about ECG features in these patient. The case we described allows to observe dynamic ECG alterations in a patient with electro-induced ventriculograms Case Description: A 90-year-old male was admitted to the emergency room for important fatigue associated with severe bradycardia (25/min). His cardiovascular history was silent, and his past medical history was characterized by high blood pressure, chronic pulmonary obstructive disease and anemia due to iron deficiency. The ECG showed second degree AVB type 2, with phases of 2:1 AVB and paroxysmal third degree AVB on continuous monitoring. The routine blood tests showed normal T troponin and BNP was 420 pg/mL. The echocardiogram revealed normal biventricular dimensions and systolic function with moderate aortic valve stenosis. The patient underwent urgent permanent DDD pacemaker implantation without previous isoproterenol administration. During the procedure he referred important pain on the site of the wound, and he became confused and agitated. The procedure was complicated by massive pneumothorax that needed quick decompression. On the 2nd day after pacemaker implantation the ECG revealed electro-induced atrium-guided ventriculograms and began to modify with only mild ST-segment elevation in V2 and initial T-wave inversion from V3 to V6 and in I - II - aVF. On the next days, T-waves became deeper and QTc prolonged to 540 ms. These abnormalities were then gradually resolved on the 11 th day. Mild transient attenuation of the amplitude of the QRS complexes in V2 – V3 leads on day 1 could be reported. Another echocardiogram was then performed, which showed new apical akinesis with "apical ballooning" aspect and EF of 40%. TnT and BNP values increased. Coronary angiogram was not performed due to patient rejection, so that coronaropathy could not be excluded with certainty. Nevertheless, the patient had only high blood pressure as cardiovascular risk factor and that the probability of the diagnosis of takotsubo cardiomyopathy was assessed of 76, 9% by InterTAK diagnostic score, so that we considered Takotsubo syndrome the most likely diagnosis. Therefore, the patient's therapy was then optimized with an increase in the dosage of ACE inhibitors. At one month follow-up the ECG remained stable, and the echocardiogram showed a preserved ejection fraction (EF = 55%), without alterations of the segmental contractility. BNP and TnT values were normal. Therapy was left unmodified. Conclusions: Takotsubo syndrome should be consider a rare but possible complication of pacemaker implantation. This is true especially for patients affected by frailty and cognitive impairment. There are no specific ECG criteria for takotsubo syndrome in patients with electro-induced ventriculograms, but anomalies of the repolarization are similar to those in patients with spontaneous ventricular activity. Transient attenuation of the QRS complexes voltages could be seen even just in the precordial leads and it is generally present in the very acute phase.